Translation Memory from the Swedish NAO - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
A translation memory received from a translator at the Swedish NAO

Översättningsminne mottaget av översättare på Riksrevisionen i december 2017
Översättningsminne från Riksrevisionen
Keywords: Financial Audit; Finansiell revision; Management Audit; Förvaltningsrevision; Economic systems and development; Ekonomiska system och ekonomisk utveckling; Social Sciences; Samhällsvetenskap; Economics; Nationalekonomi; Languages and Literature; Språk och litteratur; Public Administration Studies; Studier av offentlig förvaltning